Fabrication of expanded thermoplastic starch reinforced by randomly oriented short abaca fibers - Lapuz, Anniver Ryan Pablo; Diaz, Leslie Joy L. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The excessive amount of disposable single used polymer-based foam packaging materials has led to serious demands for biodegradable materials made from renewable resources. These biodegradable polymers can be produced from starch obtained from agricultural by-products. Cassava Lakan I variety is a high starch content source (25%) locally grown in the Philippines that has a huge potential for this application. This study was conducted to determine the operating conditions needed to transform a crystalline starch into a thermoplastic starch that would behave similarly with a petroleum based plastic. Preliminary results adopting the batter formulation of Vasquez (2013) showed two viable conditions in fabricating the expanded thermoplastic starch (ETPS) using a heated compression molding. The operating condition heated at 180ºC for 30 seconds showed a higher tensile strength than operating condition of 150ºC heated for 90 seconds. Randomly oriented short abaca fibers in a mesh form were incorporated via sandwiched technique enabling a more uniform distribution of fibers compared to directly mixed abaca fibers in the starch batter. Short randomly oriented abaca fibers mesh were prepared using 10 mm and 20 mm fiber length while taking into consideration the critical length of abaca fiber in the ETPS that is at 18 mm fiber length. The fiber mesh was used to reinforce ETPS at 3%, 5%, and 7% fiber volume. Among the different formulations in the fiber volumes and fiber lengths, the combination of 5% fiber volume and 10 mm fiber length has resulted to the highest tensile strength and modulus of elasticity of 1.034± 0.237 MPa and 14.933 MPa respectively. A 3.56% increase in tensile strength and a 160 times increase of modulus of elasticity of the ETPS. Compared to the commercial Styrofoam, an increase of 156.49% in the tensile strength was observed and a comparable thermal conductivity with a difference of 9.62%. However, further studies have to be conducted to minimize the huge gap in the water absorption capacity and density of the expanded TPS composite from commercial Styrofoa
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Starch -- Thermal propertie; Thermoplastic; Biopolymer; Abaca (Fibe.